Closing Peru's Ethnic Gaps Amidst Sustained Economic Growth - Chavez, Carlos (IMF Working Papers; Working Paper, 2022)
We analyze the recent evolution of ethnic economic inequality in Peru, a major source of social discontent in the country. Household survey data indicates that recent decades of high output growth also witnessed a substantial narrowing of socioeconomic gaps among ethnicities. Most notably, the Mestizo ethnic group surpassed the White group in income per capita, and Native American also experienced a relative improvement. Mincerian regression analysis suggests that the main contributors to these developments were rural-to-urban migration and increased education. Based on our statistical findings, we propose enhancing education and other public services, increasing government revenues, lowering informality, and promoting competition as the main public policies that could accelerate the ongoing narrowing of ethnic gaps.